EDUCATION ON PROCESSING PLASTIC WASTE INTO ECOBRICKS IN BERUA SUBDISTRICT AND BONTODURI SUBDISTRICT MAKASSAR CITY: THE EDUCATION ON PROCESSING PLASTIC WASTE INTO ECOBRICKS IN BERUA SUBDISTRICT AND BONTODURI SUBDISTRICT MAKASSAR CITY - Sri Wulandari (Politeknik Kelautan dan Perikanan Sorong, 2023)
Plastic is one of the factors causing environmental damage due to human hands. Plastic can become dangerous microplastics if mixed with soil and water because it becomes toxic to the human body. Efforts can be made by innovating to turn plastic waste into ecobricks. Ecobricking is a technique of turning plastic waste into bricks, filling bottles with compacted plastic waste. This community service aims to educate the community, especially in Berua Village and Parang Tambung Village in the management of plastic waste into household furniture with ecobrick techniques. The implementation method used is the approach method starting from the preparation, implementation, observation, evaluation and reflection stages on December 11, 2022 in Berua Village and on March 5, 2023 in Parang Tambung Village with a total of 60 participants. The result is that the community is given education about the types of plastics so that they understand how to categorize them, education about 4R-based waste management, namely reduce, reuse, recycle, and replace. The conclusion of this PKM is that the community knows and understands about the ecobrick technique seen from the results of the evaluation conducted.